Assessing new SSR markers for utility and informativeness in genetic studies of brown rust fungi on wheat, triticale, and rye. (10th February 2021) - Czajowski, Grzegorz; Kosman, Evsey; Słowacki, Piotr; Park, Robert F.; Czembor, Paweł
Abstract: The aim of the present study was to validate new simple‐sequence repeat (SSR) markers and use them to assess genetic variability among 24 isolates of Puccinia triticina collected from wheat (Pt‐wheat) and triticale (Pt‐triticale), and 15 isolates of P . recondita f. sp. secalis (Prs) collected from rye. The Pt and Prs isolates were tested for virulence on a set of 35 Thatcher wheat near‐isogenic lines, eight rye lines with known resistance genes, and 53 triticale cultivars with uncharacterized leaf rust resistance. Molecular genotypes were determined using a newly developed set of 34 SSR microsatellite primer pairs. All SSR markers tested on Pt isolates successfully amplified fragments of appropriate size. When tested on the Prs isolates, 21 out of the 34 Pt SSRs amplified expected fragments. Sixteen of these 21 SSRs were polymorphic, providing for the first time microsatellite markers to study genetic variation in Prs. Based on virulence data, variation among Prs isolates was low, probably due to the small number of rye differential lines available. Much higher variation for virulence was observed within the collection of Pt isolates from wheat and triticale, and two separate groups were established with mixed host origin. Substantial genetic variation was detected among the isolates studied with the SSR markers, assuming two different models of SSR evolution (infinite alleles model and stepwise mutation model). The newly developed set of SSR markers proved their effectiveness in detecting genetic variation and should be useful in further population genetics investigations of the two pathogens. Abstract : New simple‐sequence repeat (SSR) markers enable genetic studies of leaf rust on wheat and triticale ( Puccinia triticina ) and on rye ( P. recondita f. sp. secalis ).